2021
DOI: 10.3390/catal11111410
|View full text |Cite
|
Sign up to set email alerts
|

Application Potential of Cyanide Hydratase from Exidia glandulosa: Free Cyanide Removal from Simulated Industrial Effluents

Abstract: Industries such as mining, cokemaking, (petro)chemical and electroplating produce effluents that contain free cyanide (fCN = HCN + CN−). Currently, fCN is mainly removed by (physico)chemical methods or by biotreatment with activated sludge. Cyanide hydratases (CynHs) (EC 4.2.1.66), which convert fCN to the much less toxic formamide, have been considered for a mild approach to wastewater decyanation. However, few data are available to evaluate the application potential of CynHs. In this study, we used a new Cyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…These effects have to be investigated for various types of samples. While studying the degradation of fCN by CynHs, we observed that wastewater components such as sul des or thiocyanates did not signi cantly inhibit the enzyme [25], which is encouraging. Sul des and sul tes (both from 1 mg/L) strongly interfere with the picric acid method, and thiocyanates in a concentration of over 0.05 mg/L affect the results obtained with the above kit, along with other ions [8].…”
Section: Compoundmentioning
confidence: 60%
See 2 more Smart Citations
“…These effects have to be investigated for various types of samples. While studying the degradation of fCN by CynHs, we observed that wastewater components such as sul des or thiocyanates did not signi cantly inhibit the enzyme [25], which is encouraging. Sul des and sul tes (both from 1 mg/L) strongly interfere with the picric acid method, and thiocyanates in a concentration of over 0.05 mg/L affect the results obtained with the above kit, along with other ions [8].…”
Section: Compoundmentioning
confidence: 60%
“…CynH (GenBank: KZV9269) from Exidia glandulosa was produced in Escherichia coli Origami B(DE3) as a fusion protein with a C-terminal His 6 -tag. Cultivation and puri cation were carried out and the activity was determined as described previously [25]. Brie y, cultivation proceeded in 2xYT medium at 37°C until optical density measured at 600 nm reached 1.0.…”
Section: Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…A simulated electroplating effluent was composed of 100 mM fCN and 1 mM AgNO 3 or 1 mM CuSO 4 . The results showed that the NitEg at a concentration of 14 µg enzyme mL −1 was sufficient to remove more than 97% fCN in the simulated electroplating effluent after 1 h. The NitEg demonstrated excellent performance in fCN solutions of up to 100 mM concentrations under alkaline conditions [29].…”
mentioning
confidence: 95%
“…Cyanide hydratases (CynHs) (EC 4.2.1.66) belong to the nitrilase family and catalyze the hydration of cyanide to formamide. Sedova et al [29] used a new CynH from Exidia glandulosa (protein KZV92691.1, namely, NitEg), which was overproduced in Escherichia coli. The cell-free extract had a specific activity of 280 U mg protein −1 , which was increased to 697 U mg protein −1 after purification via cobalt ion affinity chromatography.…”
mentioning
confidence: 99%